Proses Pengembangan Kurikulum - Karima Nabila Fajri (Pendidikan Agama Islam STIT Palapa Nusantara, 2019)
The curriculum is one component and guideline that facilitates the implementation of education in achieving its objectives. The curriculum becomes an important component in education, because it regulates all educational processes from planning to evaluation. The curriculum development process is a step to develop a curriculum, it can also be interpreted as steps to produce a curriculum or perfect an existing curriculum. In curriculum development there are supporting factors and inhibitors that influence. This study discusses the curriculum development process, the stages of curriculum development, and the supporting factors of inhibiting funds in the curriculum development process. The method used in this draft article is library research, by examining some literature on curriculum development. How can you know the curriculum development process that is being carried out to develop the curriculum.